Media policies and the quest for freedom of expression in Tunisia's democratic process - El Sellami, Olfa Rashid (AUC Knowledge Fountain, 2015)
This thesis examines media policies in the context of Tunisia’s democratic process. It describes and analyzes these policies and to what extent they answer the quest for freedom of expression. The relation between media policies and democratization shows the role of media policy change in enhancing the democratic process and its consolidation. While applying several theories, this study emphasizes the role of free press for a sustainable democracy. The significance of this study is to call attention towards the function and the responsibility of media freedom during the country’s transitional period to be a contributor to the consolidation of policy change. The UNESCO Media Development Indicators (MDI) are used as a model of assessment to the Tunisian media landscape post the revolution 2011. This thesis uses a qualitative research method. Data is collected through in-depth interviews and observation, and content analyses are then used to investigate media policies in Tunisia’s transition and provide a comprehensive understanding about the various challenges impeding the implementation of these policies. The analyses aim also at formulating clear recommendations for a better implementation of media policies. The interviews with media professionals document the perspectives of some media players in this transitional period. Among the main findings of the research are: liberalizing the media is unattainable without training journalists to overcome the entrenched inheritance of authoritarianism; a free media safeguarded by the constitution and enhanced by sound policies should be implemented and practiced in field so that to empower a real democratization.